MRI findings in two West Highland White Terrier dogs with hepatic encephalopathy secondary to portosystemic shunt. Issue 3 (4th July 2019) - Fernandes, Ricardo; Driver, Colin; Rose, J H; Rusbridge, Clare
Abstract : A portosystemic shunt is an abnormal communication between the portal vascular system and the systemic circulation. A significant number of clinical signs associated with portosystemic shunting result from hepatic encephalopathy (HE); a syndrome encompassing neurological signs such as including changes in behaviour, ataxia, unresponsiveness, pacing, circling, blindness, seizures, coma and death. We present two West Highland White Terrier dogs diagnosed with HE based on clinical signs, bile acid stimulation test and imaging of the abnormal vessel communicating the portal and the systemic circulation. Magnetic resonance sequences of the brain revealed a poorly marginated and diffuse, bilateral and symmetric hyperintense lesions on T2‐weighted, fluid attenuation inversion recovery and diffusion‐weighted sequences relative to the brain parenchyma including the medial longitudinal fasciculus and reticular formation in the brainstem. No abnormalities were detected on T1‐weighted sequences.